1987
DOI: 10.1007/bf00005349
|View full text |Cite
|
Sign up to set email alerts
|

The influence of prey communities on fish species assemblages on artificial reefs in Puget Sound, Washington

Abstract: SynopsisResearch on eleven artificial reefs in Puget Sound, Washington examined the relative importance of reefproduced prey items to recreationally important reef fish species assemblages. The colonization of potential prey items, and fish species assemblages to ten artificial reefs were examined for the reefs first two to five years, and observations were conducted on an eleventh reef during its forty-ninth productive year. Fish species became more abundant, or were seen more frequently on reef habitats whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 15 publications
0
20
0
2
Order By: Relevance
“…On older reefs, fishes predominantly fed on algalmat-associated species. Hueckel and Buckley (1987) also found that some fish species also fed on the surrounding sand epifauna. They concluded that artificial reef communities change over time.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…On older reefs, fishes predominantly fed on algalmat-associated species. Hueckel and Buckley (1987) also found that some fish species also fed on the surrounding sand epifauna. They concluded that artificial reef communities change over time.…”
Section: Resultsmentioning
confidence: 89%
“…Bohnsack (1989) reported that fishes associated with artificial reefs feed both on organisms associated with the reef structure and on the surrounding benthic communities. Although studies of artificial-reef fish foraging have been conducted (Davis et al, 1982;Hueckel and Stayton, 1982;Steimle and Ogren, 1982;Hueckel and Buckley, 1987;Ambrose and Anderson, 1990), the results provide no clear paradigm. It is still unknown where most of the prey organisms for reef-associated predatory fishes originate.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Probablemente, las especies más ligadas al proceso colonizador llegan buscando un hábi-tat apropiado como refugio, ya que la mayoría son de hábitos sedentarios, muy ligadas al sustrato, en un proceso similar al que propone Sale (1991), en el que las especies se reparten por el espacio habitable disponible mediante un proceso al azar. Tampoco debería descartarse el efecto de la atracción por el aumento de presas tanto de naturaleza íctica, como al Restauración del medio marino en la reserva marina de Tabarca (Alicante, España): estructura y variaciones temporales de la ictiofauna asociada al arrecife artifi cial 45 ÍNDICE aumento de presas ligado al desarrollo en complejidad y biomasa de la comunidad bentónica (Hueckel y Buckley, 1987), como se ha comprobado en algunos arrecifes artifi ciales (Foster et al, 1995;Herrera, 1998). Si bien, este efecto probablemente sea menor que el inducido por la complejidad del hábitat, ya que la mayor parte de las especies parece que se alimentan de los fondos blandos cercanos (Ardizzone et al, 1997a;Bortone y Nelson, 1995).…”
Section: Discussionunclassified